Divided by Language, but United in the Imagination? - Fehige, Joerg H. Y. (Sophia, 2022)
In my contribution to this special issue (under the title "Religions and Languages: A Polyphony of Faiths"), I draw attention to the topic of the imagination at the interface of modern science and Christian theology. The paper entertains in critical perspective the notion that language (understood broadly as any type of formalized assertive expression) divides, while the imagination (defined here broadly as inventive re-enactment of the world in a human mind) unites. While the paper is intended to be explorative, a clear thesis emerges: in its commitment to consilience, Christian theology is directed to the imagination under the pressure of the pluralizing effects of a reason that is constrained by language.